A study of interests and science process skills - Retni Sulistiyoning Budiarti; Dwi Agus Kurniawan; Putri Ayu Rivani (Jurnal Inovasi Pendidikan IPA, 2021)
This study aims to determine the differences and the relationship between interest and science process skills with 80 female students and 56 male students. This research uses quantitative methods so that this research is more systematic and objective. The sampling technique used in this study used simple random sampling. Analysis of the data used using hypotheses in the form of normality, linearity and homogeneity tests and assumption tests in the form of T test and correlation test. From the results of the T test and correlation test, it was found that there were differences and relationships between the sexes in the interests and skills of class VIIA and VIIB. In this case it is evidenced by a significant value 0.05. Thus, the higher the interest of students, the higher the skills of students according to their gender. It can be said that success can be seen from the level of understanding, mastery of the material, and student achievement. The higher the understanding and mastery as well as learning achievement, the higher the level of learning success.